Pengaruh Pemahaman Kode Etik Profesi Akuntan Terhadap Perilaku Etis Auditor (Studi Kasus Kantor Akuntan X Dan Y di Jakarta Selatan) - Al Amin, Muhamad Hafidzudin; ., Rahmaita; Sumiarti, Elni; ., Novadilastri (CV. ITTC INDONESIA, 2024)
The increasing number of cases of violations of the Accountant's Code of Ethics among the Accounting Profession is currently causing a crisis of trust in society. This research aims to determine the influence of understanding the professional code of ethics for accountants on the ethical behavior of auditors at KAP X and Y in South Jakarta. The research design uses quantitative research methods. Sampling techniques are generally carried out randomly, data collection uses primary data, namely distributing questionnaires or questionnaires that are quantitative or statistical in nature with the aim of testing predetermined hypotheses. In this research, the population is Auditors who work at Public Accounting Firms X and Y in South Jakarta using saturated sampling or census. The data analysis used in this research is analyzing quantitative data consisting of validity tests, reliability tests, classical assumption tests, simple regression and hypothesis tests with the help of the SPSS version 27 program. 9.273 with a significant value of 0.000, while ttable is 0.679, so tcount > ttable (9.273 > 0.679), then the code of ethics shows a number < 0.005 (0.000 < 0.005), Ha is accepted, meaning that partially the code of ethics has a significant effect on the auditor's ethical behavior.